A Case of Corticobasal Degeneration Studied with Positron Emission Tomography - H. Nagasawa; T. Imamura; H. Nomura; M. Itoh; T. Ido (Behavioural Neurology)
We measured cerebral blood flow, oxygen metabolism, glucose utilization, and dopamine metabolism in the brain of a patient with corticobasal degeneration using positron emission tomography (PET). The clinical picture is distinctive, comprising features referable to both cortical and basal ganglionic dysfunction. Brain imagings of glucose and dopamine metabolism can demonstrate greater abnormalities in the cerebral cortex and in the striatum contralateral to the more affected side than those of blood flow and oxygen metabolism. This unique combination study measuring both cerebral glucose utilization and dopamine metabolism in the nigrostriatal system can provide efficient information about the dysfunctions which are correlated with individual clinical symptoms, and this study is essential to diagnosis of corticobasal degeneration.